Aminopyridine derived azomethines as potent antimicrobial agents. (2021) - Mashood Ahamed, F.M.; Ali, Arshad M.; Velusamy, V.; Manikandan, M.
Abstract: Imines are synthetically accessible and structurally diverse compounds, typically obtained by facile condensation between an aldehyde, or a ketone with primary amines, sometimes known as Schiff bases. Imines contain an azomethine (-C = N) linkage that stitches together two or more biologically active aromatic/heterocyclic scaffolds to form various molecular hybrids with interesting biological properties. Schiff bases are versatile compounds with vast therapeutic applications such as antibacterial including antimycobacterial, antifungal, antiviral, antimalarial, anti-inflammatory, antioxidant, pesticidal, cytotoxic, enzyme inhibitory, and anticancer including DNA damage. Based on the above consideration an attempt has been made to synthesize Schiff bases by reacting diketones/ketoesters with substituted 2-aminopyridines. Structures of the compounds were well established by FT-IR, 1 H & 13 C NMR and mass spectral studies. Further the compounds were screened for in-vitro antimicrobial activity employing agar dilution method. All the compounds showed excellent antimicrobial activity against the bacterial and fungi pathogens.